Determinants of transaction activity in commercial real estate markets: evidence from European and Asia-Pacific countries. Issue 4 (2nd October 2017) - Devaney, Steven; McAllister, Pat; Nanda, Anupam
Abstract: Variations in transaction activity between commercial real estate markets could have important implications for investment strategies and pricing. We consider why turnover rates, a common liquidity proxy, vary between countries and over time. We examine 38 countries in Europe and Asia-Pacific over the period 2000–2014. A conceptual framework is discussed prior to estimation of panel models that use turnover rates as the dependent variable. Our results indicate that the size and wealth of a country, the risk associated with that country and the performance of its commercial real estate market are significant factors that explain transaction activity. The quality of property rights is also an important factor.